2020
DOI: 10.1007/s11145-020-10097-3
|View full text |Cite
|
Sign up to set email alerts
|

Word-to-text integration in English as a second language reading comprehension

Abstract: We assessed the relationship between word-to-text-integration (WTI) and reading comprehension in 7th grade students (n = 441) learning English as a second language (L2). The students performed a self-paced WTI reading task in Fall (T1) and Spring (T2), consisting of three text manipulation types (anaphora resolution, argument overlap, anomaly detection), divided in simple and complex passages. The passages contained proximate versus distant anaphora, explicit repetitions versus implicit inferences, and no anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
3
15
0
Order By: Relevance
“…We found clear signs that adolescents were able to monitor their comprehension when reading in the L2, as visible in increased rereading of inconsistent information. This finding is akin to other evidence with children and adults reading in their L1 (Connor et al, 2015;Hessel et al, 2021;Joseph et al, 2008;Rayner et al, 2004) and extends the evidence base on online monitoring in the L2 by adding detailed insights into adolescent readers (as previous L2 studies have either focused on younger children or adults; Hessel et al, 2021;Hessel & Schroeder, 2020; or been limited to less detailed reading time data from self-paced reading; Mulder et al, 2020). On a more general note, this finding could be considered encouraging news for all language practitioners as it indicates that adolescent learners can reliably process information from expository texts, even when reading in their L2.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We found clear signs that adolescents were able to monitor their comprehension when reading in the L2, as visible in increased rereading of inconsistent information. This finding is akin to other evidence with children and adults reading in their L1 (Connor et al, 2015;Hessel et al, 2021;Joseph et al, 2008;Rayner et al, 2004) and extends the evidence base on online monitoring in the L2 by adding detailed insights into adolescent readers (as previous L2 studies have either focused on younger children or adults; Hessel et al, 2021;Hessel & Schroeder, 2020; or been limited to less detailed reading time data from self-paced reading; Mulder et al, 2020). On a more general note, this finding could be considered encouraging news for all language practitioners as it indicates that adolescent learners can reliably process information from expository texts, even when reading in their L2.…”
Section: Discussionsupporting
confidence: 76%
“…In the eye movement record, comprehension monitoring shows in increased rereading of inconsistent compared to consistent information, a sign that readers notice and re-analyse the inconsistent information (Connor et al, 2015;Hessel et al, 2021;Joseph et al, 2008;Rayner et al, 2004). This increased rereading is important for comprehension: more pronounced slow-downs on inconsistences are associated with stronger reading comprehension (Mulder et al, 2020) and comprehension suffers when rereading is made impossible (Schotter et al, 2014). Thus, rereading of inconsistences provides an excellent window into ongoing monitoring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As previous research has found that complex syntactic text features are associated with reading comprehension difficulties in L2 child and adolescent readers (Uccelli et al, 2015a;Uccelli et al, 2015b;Phillips Galloway and Uccelli, 2019), we expected that phrase complexity, clause complexity, and anaphoric references would all negatively modulate the expected positive effect of cross-linguistic sentence integration skills on offline text comprehension. Based on similar findings in a self-paced L2 reading study in Spanish-English bilingual adolescents which found that words in more syntactically complex passages were read more slowly than words in simpler ones (Kim et al, 2018;Mulder et al, 2020), we expected a negative impact of these complex text features on online text processing. The study's hypotheses were that:…”
Section: The Current Studymentioning
confidence: 65%
“…In the current study, we therefore ask whether executive control and word processing difficulty interact in their influence on adolescents' comprehension monitoring. This question is particularly relevant for adolescents L2 learners for whom online monitoring is a strong predictor of their overall comprehension (Mulder et al, 2021). Additionally, word processing tends to be more difficult when reading in one's L2 vis-àvis L1 (Cop et al, 2015), which impacts sentence and higher-level processing (Hopp, 2017;Lim & Christianson, 2014;Pérez & Bajo, 2019;van den Bosch et al, 2018;Whitford & Titone, 2012).…”
Section: Introductionmentioning
confidence: 99%